Edukasi Mitigasi Bencana Sebagai Bentuk Kepedulian Sosial dan Penguatan Kesiapsiagan Masyarakat - Adhijaya Pendit, Saka; Dayuningsih, Dayuningsih; Oktianingsih, Teti (Civiliza Publishing, 2025)
The community must play a role in preparing for the threat of flooding through early preparation and adequate knowledge to deal with flood disasters. The knowledge possessed by individuals or communities will indirectly influence attitudes and behavior, especially in anticipating any disasters that occur. Preparedness is a crucial factor that is a focus of attention today, given that it is a determining factor in disaster risk reduction, which can be implemented and attempted early. This community service activity, held on March 24th, will provide education on disaster mitigation at the Graha Yatim and Dhuafa Orphanage, Harapan Robani Foundation.